Design Of Real Time Analysis Simulation For Two Interacting Tank Model System Using Python Programming Language - Ramli, Nurin Nafisa (Universiti Sains Malaysia, 2021)
Due to the global pandemic caused by COVID-19, institutions have adopted a digital approach to teaching, boosting the integration and application of technology in methodological adaptation. This study is one of method to implement the technology in creating new changing in engineering education. In this study, the computer programmed was used to develop the suitable simulation system on interacting tank system by employing physical mathematical modelling. The mathematical modelling of two tank was used to develop the program by considering the resistance to flow is linear. From the developed Python programmed code, the user able to interact with the model using graphical user interface know as GUI. The discussion on the interaction between the parameter of the tank related to liquid level response were further discuss in this thesis. Considering technological advancements, researchers in linked fields have created a virtual experiment platform. The virtual lab's capability must meet the requirements for theoretical experiment results. The constructed simulation's flow diagram depicts the relationship between data input, mathematical model, and output. The Python programming used include several of module to simulate the mathematical modelling. The validation of the performance of the Python developed programme was done by comparing the output results with Microsoft Excel and literature studies. The parameter that have been manipulate in this project are liquid flow rate into the tank 1 and the different on the resistance of both tank. The output of the program proves how this parameter interact with each other and it shown the interacting variable between the two-tank system. Keyword: Simulation, Python, Two Interacting Tank, Mathematical Modelling, Virtual Learning.